Peasant women and politics in Fascist Italy : the Massaie Rurali - Willson, Perry R. (Routledge, 2002)
Peasant women were the largest female occupational group in Italy between the wars. They led lives characterised by great poverty and heavy workloads, but Fascist propaganda extolled them as the mothers of the nation and the guardians of the rural worlds, the most praiseworthy of Italian women.